Peatland Management Policy: How to Build a Good Public-Private Partnership? - Zulkarnaini, Zulkarnaini; Nasution, Mimin Sundari; Meiwanda, Geovani; Istihat, Yusman; Bedasari, Hafzana (SCAD Independent, 2024)
Despite the government of Indonesia’s best efforts, several issues have arisen from the lack of policy integration on implementing comprehensive policies for appropriate peatland management. Criticism claims that many current policies put short-term financial gain ahead of long-term sustainability. This study looks at the dynamics resulting from Indonesia’s disjointed implementation of the country’s peatland policy. This research examines laws and regulations on policy concerns adopted in peatland management through a public policy and legal approach. The study’s conclusions highlight the contradictory state of Indonesia’s peatland policy, which is marked by shifts that highlight competing values—giving development and sustainability equal weight, for example. During the dry season, smoke, recurrent fires, and associated health issues are inevitable.